Fabrication of mesoporous carbon supported Ni-Mo catalysts for the enhanced conversion of glucose to ethylene glycol - Kirali, Arun Arunima; Sreekantan, Sreejith; Marimuthu, Banu (New Journal of Chemistry, 2020)
Mesoporous carbon (MC)-supported Ni-Mo catalysts with varying amounts of Ni (x= 0, 3, 6 and 9 wt%) and Mo (y= 0, 10, 15 and 20 wt%) were prepared using the wet-impregnation method and characterized. Their catalytic activity in the selective conversion of aqueous glucose solution (15 wt%) to ethylene glycol (EG) in a batch reaction was investigated. A catalyst, with 3% Ni and 15% Mo on MC showed the highest activity and selectivity. The complete conversion of glucose with 63.2% yield of EG was obtained in a reaction conducted for 6 h at 200 degrees C and 40 bar hydrogen pressure. A synergistic enhancement in catalytic performance was found when both Ni and Mo were present in the catalyst composition. The dispersion of Mo enhanced in presence of Ni and a part of Mo was reduced from +6 to lower oxidation states (+5 and +4), which imparted the acidity of the catalyst. Ni facilitated the hydrogenation activity and acid sites on Mo led to the retro-aldol reaction forming higher amounts of EG. The catalyst was found to be reusable.

Enhanced one-pot selective conversion of cellulose to ethylene glycol over NaZSM-5 supported metal catalysts - Sreekantan, Sreejith; Kirali, Arun Arunima; Marimuthu, Banu (New Journal of Chemistry, 2021)
The mesopores interconnected with microporous NaZSM-5 was synthesised by sol-gel method. Reactions involving cellulose using different bimetallic and trimetallic combinations of nickel, aluminium, and tungsten metals supported on NaZSM-5 have been carried out. Different weight percentages (wt%) of Al, Ni, and W were loaded onto the NaZSM-5 support via a wet impregnation method. The prepared catalysts were characterized using PXRD, FE-SEM, HR-TEM, BET, and XPS studies to investigate the presence of mesopores, the textural properties, the metal loading, and the active oxidation states. The catalytic activities of the xAl-yNi-zW/NaZSM-5 (where x, y, and z are the wt% values of Al, Ni, and W, respectively) supported catalysts were studied during the one-pot conversion of cellulose into ethylene glycol at 220 degrees C and with a pressure of 70 bar H-2 (at the reaction temperature) in water (as a solvent). The 5%Al-8%Ni-25%W/NaZSM-5 catalyst exhibited the highest cellulose conversion of 100%, with an ethylene glycol yield as high as 89% (C mol%) under moderate reaction conditions being reported for the first time. Al3+ in the catalyst hydrolyzed cellulose, and W5+ species acted as acid centres that facilitated the retro-aldol condensation reaction and eventually led to an increased EG yield in the presence of Ni. The catalyst was moderately stable after four consecutive runs for 6 h at 220 degrees C and at a H-2 reaction pressure of 70 bar, though a 12 h reaction resulted in the highest EG yield. The high yields under moderate reaction conditions promise an energy-efficient and economically feasible process.